Exploring the relationship between foreign language anxiety and students’ online engagement at UK universities during the Covid-19 pandemic - O'Reilly, Jelena (2022)
Although foreign language anxiety (FLA) and student engagement have both been found to have significant effects on a number of behavioural and academic outcomes for language students (Awan et al. 2010, Gargalianou et al. 2016). FLA is poorly understood in university students studying English as a second language. However, limited research shows it is present (Haley et al. 2015). Additionally, the relationship between FLA and student engagement has seldom been explored. Therefore, the present exploratory study investigated the relationship between FLA and online learning in university students, particularly focusing on online learning as the new mode of instruction since the start of the COVID-19 pandemic. We wanted to explore to what extent FLA is present among international students studying in L2 English at UK universities and whether FLA affects engagement with online learning. We tested 65 international students, studying at UK universities, using two newly developed scales for measuring FLA and student engagement with online learning. Participants completed an online questionnaire with background questions, the FLA scale, and the students’ engagement scale. The results of our multiple linear regression analyses suggest that FLA has a significant negative influence on students’ engagement with online learning.